"Secular light curves of 25 members of the themis family of asteroids, suspected of low level cometary activity". (March 2017) - Ferrín, Ignacio; Pérez, Martín; Rendón, Juan
Abstract: From 1996–2015 sixteen main belt asteroids were discovered exhibiting cometary activity (less than one per year), all of them during searches at the telescope. In this work we will explore another way to discover them. We reduced 192.016 magnitude observations of 165 asteroids of the Themis family, using data from the astrometric-photometric database of the Minor Planet Center, MPCOBS, and measuring the absolute magnitudes from the phase plots. 25 objects of 165 (15.2%), exhibited bumps or enhancements in brightness that might indicate low level cometary activity. Since activity repeats at the same place in different orbits and in many occasions is centered at perihelion, activity might be due to water ice sublimation. We do not find support for a correlation between short rotational periods (3–4 h), and cometary activity, although we find an excess of fast rotators. Highlights: We reduced 192.016 magnitude observations of 165 asteroids of the Themis family. The calculated absolute magnitude vs time should be flat for inactive objects. 25 objects (15.2%) exhibit enhancements interpreted as low level cometary activity.